Newborn Screening for Glutaric Aciduria-II: The New England Experience - Sahai, I. (Springer Berlin Heidelberg, 2013)
Newborn screening (NBS) using tandem mass spectrometry (MS/MS) permits detection of neonates with Glutaric Aciduria-Type II (GA-II). We report follow-up of positive GA-II screens by the New England Newborn Screening Program. Methods: 1.5 million infants were screened for GA-II (Feb 1999–Dec 2012). Specialist consult was suggested for infants with two or more acylcarnitine elevations suggestive of GA-II. Results: 82 neonates screened positive for GA-II, 21 weighing > 1.5 kg and 61 weighing ≤ 1.5 kg. Seven (one weighing < 1.5 kg), were confirmed with GA-II. Four of these had the severe form (died < 1 week). The other three have a milder form and were identified because of newborn screening. Two (ages > 5 years) have a G-Tube in place, had multiple hospitalizations and are slightly hypotonic. The third infant remains asymptomatic (9 months old). Two GA-II carriers were also identified. The remaining positive screens were classified as false positives (FP). Six infants (> 1.5 kg) classified as FP had limited diagnostic work-up. Characteristics and outcomes of all specimens and neonates with a positive screen were reviewed, and marker profiles of the cases and FP were compared to identify characteristic profiles. Conclusion: In addition to the severe form of GA-II, milder forms of GA-II and some GA-II carriers are identified by newborn screening. Some positive screens classified as FP may be affected with a milder form of the disorder. Characteristic GA-II profiles, quantified as GA-II indexes, may be utilized to predict probability of disorder and direct urgency of intervention for positive screens.